Proximal row carpectomy versus four-corner arthrodesis: a retrospective comparative study - Richard Chan; Justine Goursat; Mathilde Payen; Matthieu Lalevée; Kamel Guelmi (Journal of Plastic Surgery and Hand Surgery)
Background: Four-corner arthrodesis with scaphoid excision (FCA) and proximal row carpal resection (PRC) are frequently performed in wrists with post-traumatic Scaphoid Non- Union Advanced Collapse (SNAC)/Scapho-Lunate Advanced Collapse (SLAC) osteoarthritis. The aim of this study was to compare the clinical outcomes of these two procedures.